Risk creating and risk reducing: Community perceptions of supervised consumption facilities for illicit drug use. (17th February 2017) - Kolla, Gillian; Strike, Carol; Watson, Tara Marie; Jairam, Jennifer; Fischer, Benedikt; Bayoumi, Ahmed M.
Abstract : Progressive public health authorities in high-income countries have advocated supervised consumption facilities, where people who use illicit drugs can consume them in a hygienic, supervised environment, as a way of reducing drug-related risks to both people who use drugs and communities. However, the planning of such facilities has often met with strong reactions from the local community. 'Not in my backyard' (NIMBY) type reactions are frequently encountered and public opinion polling is limited in its ability to provide detailed insights into the reasons why people support or oppose these facilities in Toronto and Ottawa. We explore perceptions of residents and business representatives to the proposed implementation of supervised consumption facilities, and examine their perceptions of risks from these facilities. We collected qualitative data from 2008–2010 using focus groups and interviews with 38 residents and 17 business representatives in these two large Canadian cities lacking supervised consumption facilities. We used thematic analysis to examine expressed benefits and risks regarding supervised consumption facilities amongst community members. These participants saw these facilities as potentially risk-reducing, but recognised that the facilities could also create risks for their communities. While community members accepted that facilities could have positive health effects, they expressed a level of concern regarding the risk of public nuisance associated with supervised consumption facilities that seemed unwarranted based on the existing evidence. Discussions on the risks involved in the establishment of supervised consumption facilities should move beyond a focus on the benefits to facility users, to exploring community-level benefits and risks, and integrate evidence regarding actual risk experiences from other locations. Similar approaches may apply to NIMBY concerns related to other contentious issues.